Adult height in patients with childhood‐onset inflammatory bowel disease: a nationwide population‐based cohort study. Issue 8 (4th March 2020) - Mouratidou, Natalia; Malmborg, Petter; Sachs, Michael C.; Askling, Johan; Ekbom, Anders; Neovius, Martin; Smedby, Karin E.; Sävendahl, Lars; Ludvigsson, Jonas F.; Olén, Ola
Summary: Background: Growth retardation is well described in childhood‐onset inflammatory bowel disease (IBD). Aims: To study if childhood‐onset IBD is associated with reduced final adult height. Methods: We identified 4201 individuals diagnosed with childhood‐onset IBD 1990‐2014 (Crohn's disease: n = 1640; ulcerative colitis: n = 2201 and IBD‐unclassified = 360) in the Swedish National Patient Register. Results: Patients with IBD attained a lower adult height compared to reference individuals (adjusted mean height difference [AMHD] −0.9 cm [95% CI −1.1 to −0.7]) and to their healthy siblings (AMHD −0.8 cm [−1.0 to −0.6]). Patients with Crohn's disease (CD) were slightly shorter than patients with ulcerative colitis (UC; −1.3 cm vs −0.6 cm). Lower adult height was more often seen in patients with pre‐pubertal disease onset (AMHD −1.6 cm [−2.0 to −1.2]), and in patients with a more severe disease course (AMHD −1.9 cm, [−2.4 to −1.4]). Some 5.0% of CD and 4.3% of UC patients were classified as growth retarded vs 2.5% of matched reference individuals (OR 2.42 [95% CI 1.85‐3.17] and 1.74 [1.36‐2.22] respectively). Conclusion: Patients with childhood‐onset IBD on average attain a slightly lower adult height than their healthy peers. Adult height was more reduced in patients with pre‐pubertal onset of disease and in those with a more severe disease course.